The role of contact and the perception of threat in prejudice towards Syrians in Turkey - Özkeçeci, Hediye Hilal. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The study explored the relationship between contact, threat perceptions and prejudice in the context of Syrian refugees in Turkey by using the propositions of Integrated Threat Theory (ITT; Stephan & Stephan, 2000). A total of 310 participants from Şanlıurfa and Istanbul were surveyed. In Istanbul, two groups with high and low refugee exposure were selected. The results showed that quality of contact was related negatively to perceived realistic and symbolic threat, negative stereotyping, negative affect, and social distance, and positively to feelings of warmth towards Syrians. Realistic threat negatively predicted warmth feelings and symbolic threat positively predicted social distance, whereas negative stereotyping predicted greater social distance and negative affect, and colder feelings. Realistic threat mediated the contact quality and feelings, whereas symbolic threat mediated contact quality and social distance. Finally, negative stereotyping mediated the relationship between quality of contact and each prejudice variable. Contact quality did not moderate the relationship between contact quantity and prejudice variables. Among threat variables, negative stereotyping had the strongest relationship with each prejudice variable. Group differences shed light on the role of contact quality and quantity on perceptions of threat and prejudice. Implications of the results for current socio-political environment of Turkey are highlighted.
Keywords: Threat (Psychology) -- Syrian.; Prejudices -- Turkey.; Prejudices -- Syrian.; Social psychology -- Cross-cultural studies.